Knowledge governance mechanisms’ influence on repatriate knowledge sharing - Yli-Pietilä, Eemil (fi=Turun yliopisto|en=University of Turku|, 2018)
This study researches the repatriate knowledge governance in multi-national enterprises in pharmaceutical industry. The purpose of this study is to examine, how different knowledge governance mechanisms influence the repatriate knowledge sharing and which factors deter this knowledge sharing. The study was conducted as qualitative interview research. The theoretical framework is based on the previous literature and empirical studies on knowledge sharing, knowledge governance mechanisms and repatriates. The data for empirical research was conducted in the Finnish subsidiary of a multi-national pharmaceutical enterprise in April 2018. 5 interviewees were chosen: 1 HRM-specialist and 4 repatriates, of which one repatriate was excluded for not filling the criteria on the analyzing phase. The interviews were conducted with a semi-structured method ja and the questions were based on the themes previously discusses in the literature and empirical research. The conducted interviews were transcribed and analyzed by themes. This study confirms that knowledge governance mechanisms of HR influence the repatriates’ motivations and opportunities of knowledge sharing and that knowledge sharing is deterred by certain factors. This study proposes that HR and organization should use several different mechanisms to influence the repatriate knowledge sharing and make these measures coherent by offering them to all of the repatriates. This study suggests that organizations should increase the level of repatriate knowledge sharing training and connect their evaluation and bonus systems to include knowledge sharing also. In addition, organizations should offer IT-based systems, in which the repatriates can share knowledge effectively and also use the repatriates as mentors to allow intra-organizational knowledge sharing. It should also be assured that the repatriates have an opportunity to decrease the physical and mental distance to their former host facility to maintain their networks. It was also found in this study that physical distance, inability to access the knowledge and questioning the repatriate knowledge deterred knowledge sharing. This study proves that repatriate knowledge sharing can be influenced by knowledge governance mechanisms of the HR, if they are applied correctly. To generalize these findings to other fields of industries, though, further research is needed.